Network distributed information assets detection method based on Artificial Intelligence. Issue 1 (January 2021) - Chen, Ze; Liu, Weina; Xi, Bo; Guo, Yuling
Abstract: Proposes a network distributed information assets detection method based on artificial intelligence. Through mining the characteristics of network distributed information assets, scanning information assets in depth, detecting assets, summarizing the characteristics of information assets, and optimizing the depth scanning mode of network information assets, the research goal of rapid and accurate detection of network distributed information assets is realized. The simulation results show that the proposed network distributed information assets detection method based on artificial intelligence has faster detection speed and higher detection accuracy, so as to meet the requirements of large-scale information detection and solve more complex problems.